L'evoluzione delle Stazioni Totali: quarant'anni di innovazione Topcon - Toppi, Massimiliano; Passarelli, Sauro (GEOmedia, 2018)
A 40-year history, from the introduction of the first total station model, so named because it introduced an absolute innovation compared to the combination theodolite-EDM, up to the last generations of robotic instrumentation for which the involvement of operator is reduced to the minimum terms. A long and unstoppable series of innovations, from recording on memory cards to the first motorized models; from the operating system embedded to the reflectorless measurement, up to the introduction of the images and the "Capture Reality” concept and the combined laser scanning measurement, a real revolution in the world of surveying instrumentation. What will be the next frontier?